2020
DOI: 10.1177/0011128720903047
|View full text |Cite
|
Sign up to set email alerts
|

Examining How Testosterone and Cortisol Influence the Relationship Between Strain, Negative Emotions, and Antisocial Behavior: A Gendered Analysis

Abstract: This study provides a test of General Strain Theory by examining the relations between strain, negative emotions, and biological hormones in the prediction of antisocial behavior across gender. Findings from a diverse sample of 512 undergraduate students reveal that strain and the ratio between testosterone to cortisol reactivity are associated with higher levels of antisocial behavior in males, but not females. In contrast, the effect of depressive symptoms on antisocial behavior is stronger at higher levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 75 publications
(172 reference statements)
0
8
0
2
Order By: Relevance
“…First, the articles highlight the need to study sub-groups of individuals and behavior. Cooke et al (2020), Ling et al (2020), and Fox et al (2020) all detected sex differences in relationships between biological factors and antisocial behavior. In addition, two studies in this special issue (Fox et al, 2020; Ling et al, 2020) examine psychopathy or CU traits, rather than antisocial behavior more generally.…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…First, the articles highlight the need to study sub-groups of individuals and behavior. Cooke et al (2020), Ling et al (2020), and Fox et al (2020) all detected sex differences in relationships between biological factors and antisocial behavior. In addition, two studies in this special issue (Fox et al, 2020; Ling et al, 2020) examine psychopathy or CU traits, rather than antisocial behavior more generally.…”
mentioning
confidence: 90%
“…A second common theme is the need to examine interactions between biological, psychological, and social risk factors. Four of the studies found some evidence of interactions between biological and social risk factors (Cooke et al, 2020; Farrington, 2020; Fox et al, 2020; Portnoy et al, 2020). As demonstrated by these articles, neither biological, psychological, nor social risk factors alone are likely to explain the etiology of criminal behavior and related outcomes.…”
mentioning
confidence: 99%
See 3 more Smart Citations